2013
DOI: 10.1590/s1516-14392013005000136
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of HA-316L SS biocomposites in aqueous solutions

Abstract: 316L stainless steel and Hydroxyapatite (5, 20 and 50 wt. (%) HA)-316L stainless steel composites were fabricated by mechanical alloying technique, pressing and sintering from 316L and HA powders. The corrosion behavior of both sintered 316L and HA-316L composites was evaluated by electrochemical techniques in simulated body fluid (Ringer's solution) and in 0.1M HCl solution which simulates occluded cell corrosion conditions. The results indicate that 316L stainless steel and HA-316L composites are passive in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
1
9
1
Order By: Relevance
“…In the only other relevant report, Trelewicz 21 reported a single set of polarization scans for SLM 316L relative to wrought 316L, suggesting that SLM 316L presented 'reduced passivity' in 0.1 M HCl. However the data reported in that study does not resemble the typical polarization response of 316L in 0.1 M HCl, 24,25 the polarization response being possibly influenced by crevice corrosion. Furthermore, more extensive corrosion data or its reproducibility (either by duplicate data or testing, or by the presentation of data with error analysis or error bars) has not been presented in any works to date.…”
contrasting
confidence: 55%
“…In the only other relevant report, Trelewicz 21 reported a single set of polarization scans for SLM 316L relative to wrought 316L, suggesting that SLM 316L presented 'reduced passivity' in 0.1 M HCl. However the data reported in that study does not resemble the typical polarization response of 316L in 0.1 M HCl, 24,25 the polarization response being possibly influenced by crevice corrosion. Furthermore, more extensive corrosion data or its reproducibility (either by duplicate data or testing, or by the presentation of data with error analysis or error bars) has not been presented in any works to date.…”
contrasting
confidence: 55%
“…The cathodic polarization curve was associated with a reduction of oxygen that was dissolved while at lower values of potentials and related to reduction of water. It was observed that the increase of HA content in 316L improved the corrosion resistance of stainless steel composites [31,32]. In the current investigation, it was made clear that chromium diffused from 316L to HA.…”
Section: Electrochemical Analysissupporting
confidence: 47%
“…However, the corrosion current densities for both of the FGMs were in the order of 10 -6 or less. That is characteristic of high-quality corrosion resistant materials for bioimplants (Table 2) [32]. The corrosion potential was found in the negative region for both FGMs.…”
Section: Electrochemical Analysismentioning
confidence: 78%
See 1 more Smart Citation
“…It was stated that these materials exhibit high corrosion resistant in Ringer's solution with corrosion current density in the order of 10 -6 A•cm -2 . The corrosion resistance decreases with increasing HA content [9].…”
Section: Introductionmentioning
confidence: 92%